2010
DOI: 10.1258/jms.2009.009058
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Condylomas, Anal Squamous Intraepithelial Neoplasms and Screening: A Review of the Literature

Abstract: Anal squamous intraepithelial lesions (ASILs) are the precursors to anal cancer. Human papillomavirus infection has a direct link to ASIL formation and is responsible for up to 80% of anal cancers. But while much importance has been focused on targeting cancer precursors in the cervix, relatively little concern has been afforded to the anal canal. With the advent of cervical Pap smear screening in various regions, the incidence of cervical cancer has declined. However, marked similarities in the biological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
(68 reference statements)
1
26
0
1
Order By: Relevance
“…Although epidemiologic data have suggested that the prevalence of anorectal dysplasia and carcinoma in this population were similar to that of dysplasia and cancer of the cervix in women before the widespread implementation of cervical Papanicolau (Pap) screenings (Oon & Winter, 2010), more recent studies have indicated that anal cancer is now more common than cervical cancer in women (Goldstone & Moshier, 2010).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Although epidemiologic data have suggested that the prevalence of anorectal dysplasia and carcinoma in this population were similar to that of dysplasia and cancer of the cervix in women before the widespread implementation of cervical Papanicolau (Pap) screenings (Oon & Winter, 2010), more recent studies have indicated that anal cancer is now more common than cervical cancer in women (Goldstone & Moshier, 2010).…”
mentioning
confidence: 84%
“…Because men who have HPV do not always have symptoms of the disease, the absence of visible genital lesions during a physical examination may preclude an accurate diagnosis (Bertram & Niederhauser, 2008;Oon & Winter, 2010). High rates of anal cancer have recently been observed in gay and bisexual men in whom high rates of risky sexual behavior (e.g., receptive anal intercourse with multiple partners, smoking, drug use) along with concurrent HPV infection were also prevalent (Lindsey et al, 2009;Reed et al, 2010).…”
Section: Knowledge Of Msm Regarding Screeningmentioning
confidence: 99%
“…1 Current screening for anal dysplasia is limited to human immunodeficiency virus (HIV)-positive men who have sex with men. 2 Guidelines have not been established for other potential at-risk patient populations.…”
Section: Q7mentioning
confidence: 99%
“…Anal smears and anoscopy are under investigation for AIN screening in high-risk subjects [ 70 ]. There is no treatment for HPV infection, but locally destructive treatments are used for warts and may reduce infectivity.…”
Section: Human Papillomavirusesmentioning
confidence: 99%